Efektivitas pelayanan KIE farmasi terhadap sikap penggunaan tanaman obat keluarga (TOGA) pada ibu rumah tangga - Zuhra, Meutia; Mariyati, Mariyati; Rahmi, Aulia; Maulida, Aula (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Family medicinal plants are one of the efforts to increase community participation in health development. The use of family medicinal plants has not been optimally socialized, counseling, information, and education are needed by health workers, especially pharmacists, in the use of family medicinal plants so that their use is safe and effective. Purpose: To determine the effectiveness of pharmaceutical counseling, information, and education on attitudes towards the use of medicinal plants among housewives. Method: Quantitative research using a pre-experimental design (one group pre-test and post-test) on 153 productive-age housewives (20-60 years) in Lhokseumawe City. The dependent variable in this study is attitude, while the independent variables are counseling services, information, and pharmacy education. The research instruments used were questionnaires and educational media, namely leaflets. Data analysis included univariate and bivariate with paired t-tests on normally distributed data, if not normally distributed, the Wilcoxon test was used. Results: The age of the sample was dominated by 20-30 years of age with 63 participants (41.2%) and the majority had a high school education with 39 participants (39.2%). The attitude of using family medicinal plants during the pre-test was in the positive category with 48 respondents (31.4%), but after being given the intervention, the post-test score of positive attitudes increased by 142 respondents (92.8%). In addition, the average pretest score, the attitude of using family medicinal plants was 18.38 with a standard deviation of 4.97, but during the posttest it became 26.75 with a standard deviation of 4.97. This shows an increase in the attitude score of using family medicinal plants after receiving counseling, information, and pharmaceutical education services. Conclusion: There is a difference in the attitude of using family medicinal plants in housewives after being given counseling, information, and pharmaceutical education services by pharmaceutical personnel with a p-value (0.000). Suggestion: Counseling, information, and pharmaceutical education can be applied in traditional health service programs as motivation for cultivating family medicinal plants at home, one of the efforts to increase community independence in treatment. Keywords: Attitude; Counseling; Education; Family Medicinal Plants; Housewives; Information. Pendahuluan: Tanaman obat keluarga (TOGA) merupakan salah satu upaya meningkatkan peran masyarakat dalam pembangunan kesehatan. Pemanfaatan TOGA belum tersosialisasikan secara maksimal, dibutuhkan konseling, informasi, dan edukasi (KIE) oleh tenaga kesehatan, khususnya farmasi dalam pemanfaatan TOGA agar dalam penggunaannya aman dan efektif. Tujuan: Untuk mengetahui efektifitas KIE farmasi terhadap sikap penggunaan tanaman obat keluarga (TOGA) pada ibu rumah tangga. Metode: Penelitian kuantitatif menggunakan desain eksperimental pre eksperimental (one group pretest and posttest) pada 153 ibu rumah tangga usia produktif (20-60 tahun) di Kota Lhokseumawe. Variabel dependen dalam penelitian ini adalah sikap, sedangkan variabel independen yaitu pelayanan KIE farmasi. Instrumen penelitian yang digunakan berupa lembar kuesioner dan media edukasi yaitu leaflet. Analisis data yang dilakukan meliputi univariat dan bivariat dengan paired t-test pada data yang berdistribusi normal, jika tidak berdistribusi normal digunakan uji Wilcoxon Hasil: Usia sampel didominasi 20-30 tahun sebanyak 63 partisipan (41.2%) dan mayoritas menamatkan pendidikan hingga SMA sebanyak 39 partisipan (39.2%). Sikap penggunaan TOGA ketika pretest dengan kategori positif sebanyak 48 responden (31.4%), namun setelah diberikan intervensi skor posttest sikap positif meningkat sebanyak 142 responden (92.8%). Selain itu, rerata skor pretest, sikap penggunaan TOGA 18.38 dengan standar deviasi sebesar 4.97, namun ketika posttest menjadi 26.75 dengan standar deviasi 4.97. Hal ini menunjukkan terjadi peningkatan skor sikap penggunaan TOGA setelah menerima pelayanan KIE farmasi. Simpulan: Terdapat perbedaan sikap penggunaan TOGA pada ibu rumah tangga setelah diberikan layanan KIE farmasi oleh tenaga kefarmasian dengan p-value (0.000). Saran: KIE farmasi dapat diterapkan dalam program layanan kesehatan tradisional sebagai motivasi budidaya TOGA di rumah upaya kemandirian masyarakat terhadap obat. Kata Kunci: Edukasi; Ibu Rumah Tangga; Informasi; Konseling; Sikap; Tanaman Obat Keluarga (TOGA).